Anti-inflammatory effects of budesonide in human lung fibroblasts are independent of histone deacetylase 2 - Wang X; Nelson A; Weiler ZM; Patil A; Sato T; Kanaji N; Nakanishi M; Michalski J; Farid M; Basma H; LeVan TD; Miller-Larsson A; et al. (Dove Medical Press, 2013)
Xingqi Wang,1 Amy Nelson,1 Zachary M Weiler,1 Amol Patil,1 Tadashi Sato,1 Nobuhiro Kanaji,1 Masanori Nakanishi,1 Joel Michalski,1 Maha Farid,1 Hesham Basma,1 Tricia D LeVan,1 Anna Miller-Larsson,2 Elisabet Wieslander,2 Kai-Christian Muller,3 Olaf Holz,3 Helgo Magnussen,3 Klaus F Rabe,3 Xiangde Liu,1 Stephen I Rennard1 1Pulmonary, Critical Care, Sleep and Allergy Division, Department of Internal Medicine, University of Nebraska Medical Center, Omaha, NE, USA; 2AstraZeneca R&D Molndal, Molndal, Sweden; 3Hospital Grosshansdorf, Center for Pneumology and Thoracic Surgery, Grosshansdorf, Germany Objective and design: Reduced expression of histone deacetylase 2 (HDAC2) in alveolar macrophages and epithelial cells may account for reduced response of chronic obstructive pulmonary disease (COPD) patients to glucocorticoids. HDAC2 expression and its role in mediating glucocorticoid effects on fibroblast functions, however, has not been fully studied. This study was designed to investigate whether HDAC2 mediates glucocorticoid effects on release of inflammatory cytokines and matrix metalloproteinases (MMPs) from human lung fibroblasts. Methods: Human lung fibroblasts (HFL-1 cells) were stimulated with interleukin (IL)-1β plus tumor necrosis factor (TNF)-α in the presence or absence of the glucocorticoid budesonide. Cytokines (IL-6 and IL-8) were quantified by enzyme linked immunosorbent assay (ELISA) and MMPs (MMP-1 and MMP-3) by immunoblotting in culture medium. The role of HDAC2 was investigated using a pharmacologic inhibitor as well as a small interfering ribonucleic acid (siRNA) targeting HDAC2. Results: We have demonstrated that budesonide concentration-dependently (10-10–10-7 M) inhibited IL-6, IL-8, MMP-1, and MMP-3 release by HFL-1 cells in response to IL-1β plus TNF-a. While an HDAC inhibitor significantly blocked the inhibitory effect of budesonide on human bronchial epithelial cells (HBECs) and monocytes (THP-1 cells), it did not block the inhibitory effect of budesonide on release of cytokines and MMPs from HFL-1 cells. Similarly, an HDAC2-siRNA blocked budesonide inhibition of cytokine release in HBECs, but it did not block the inhibitory effect of budesonide on HFL-1 cytokine and MMP release. Furthermore, budesonide significantly blocked release of cytokines and MMPs to a similar degree in normal and COPD lung fibroblasts as well as in HFL-1 cells exposed or not exposed to cigarette smoke extract. Conclusion: These findings suggest that, in contrast to airway epithelial cells and monocytes/macrophages, HDAC2 is not required for budesonide to inhibit MMP and cytokine release by lung fibroblasts and this inhibitory pathway appears to be intact in cultured fibroblasts from COPD patients. These results also suggest that budesonide has the potential to modulate fibroblast-mediated tissue remodeling following airway inflammation in COPD, which is mediated via an HDAC2 independent pathway. Keywords: budesonide, fibroblasts, HDAC2